2016
DOI: 10.1155/2016/8201053
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Syndrome in Patients with Diabetes Mellitus: Prevalence, Etiology, and Clinical Characteristics

Abstract: There has been substantial progress in our understanding of the ocular surface system/lacrimal function unit in the past 15 years. Keratoconjunctivitis sicca, more commonly referred to as dry eye syndrome (DES), is the most frequently encountered condition and diabetes mellitus (DM) has been identified as one of the leading causes of DES. Poor glycemic control affects both the anterior and the posterior segments of the eye and increasing prevalence of diabetes-associated DES (DMDES) has been reported in recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
156
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 46 publications
5
156
1
7
Order By: Relevance
“…Recently Ozawa et al in the years 2012 and 2015 strongly suggested that the severity of DR in males of T2D were attributed to abnormalities in neuroretinal function 16,18 . In our study frequency of DED was higher in T2D with DR, which was not noticed in previous studies [2][3][4][5] . 5 and strongly suggested that surveillance of diabetic patients and good control over blood glucose are necessary key factors for prevention of dry eye syndrome and retinopathy.…”
Section: Mean Values Of Fbs Ppbs and Hba1c By Sex And Its Associatiocontrasting
confidence: 90%
See 2 more Smart Citations
“…Recently Ozawa et al in the years 2012 and 2015 strongly suggested that the severity of DR in males of T2D were attributed to abnormalities in neuroretinal function 16,18 . In our study frequency of DED was higher in T2D with DR, which was not noticed in previous studies [2][3][4][5] . 5 and strongly suggested that surveillance of diabetic patients and good control over blood glucose are necessary key factors for prevention of dry eye syndrome and retinopathy.…”
Section: Mean Values Of Fbs Ppbs and Hba1c By Sex And Its Associatiocontrasting
confidence: 90%
“…This increase may be due to association between hormonal status and pre and postmenopausal period Our study suggests that hormones may influence the prevalence of DED in pre and post menopausal women. In our study the number of severity of DR significantly increased with respect to age and we also found relationship between sex and grades of DR. As compared to females, males are more prevalent to DR such a relation was found in Zhang et al, 2016 andOzawa et al, 2015 2, 16 .…”
Section: Mean Values Of Fbs Ppbs and Hba1c By Sex And Its Associatiomentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, in dogs, 27.8% (5 of 18) of diabetics were diagnosed with KCS and the overall average tear production among the diabetic dogs tested was low at 12.3 mm/min . Both the afferent and efferent pathways for the tearing reflex could be affected, leading to the clinical manifestation of dry eye . Poor tear film quality has also been documented in diabetic people and dogs, perhaps due to dysfunction of the parasympathetic and sympathetic innervation of the meibomian glands .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that dry eye symptoms in diabetes are correlated with the severity of the diabetic retinopathy [14,15]. In relation to this, several investigators have suggested that dry eye symptoms in diabetes are associated with peripheral polyneuropathy caused by reduced corneal sensitivity, altered homeostasis of the cornea, or ocular surface dysfunction caused by tear film instability and reduced tear secretion [16][17][18].…”
Section: Discussionmentioning
confidence: 89%